13. Neuromuscular transmission disorders in miller fisher syndrome. Issue 3 (March 2015) - Ehler, Edvard
<x xml:space="preserve">Abstract</x> Introduction Miller Fisher syndrome (MFS) is a variant of Guillain–Barré syndrome (GBS). MFS is clinically defined by trias – ophthalmoplegia, ataxia, areflexia. Antibodies against ganglioside GQ1b are bound on the nodal and paranodal sections of oculomotor nerves, sensory nerves (including spinal ganglia) and cerebellum. Ophthalmoparesis is usually severe with prominent fatiguability. In these patients neuromuscular transmission disorders are suspected. Case report A 52-year man was admitted to neurological department for progressive external ophthalmoparesis with generalized ataxia. The neurological signs and symptoms developer during 5 days with preceding upper respiratory tract infection. The first diagnosis was MFS. There was very prominent especially oculomotor fatiguability with worsening during the day and after rehabilitation, that neuromuscular transmission was suspected too. Neurophysiological investigation Motor conduction studies (including F-waves) were normal, sensory conduction studies with very low amplitude of sensory nerve action potentials. H-reflex was not elicitable. Needle EMG of biceps brachii was normal (14 days after disease onset). Repetitive stimulation (3 Hz) with recording from trapezius with 7% decrement (4th response) and from nasalis 5.8%. Axonal stimulated SF EMG with recording by concentric needle electrode from frontalis muscle presented an increased jitter −32.91 μs and 9% blocking - with the stimulation rate 3 Hz. With stimulation rate 10 Hz the jitter decreased to 26.26 μs and without blocking, with 20 Hz stimulation rate was the jitter normal (21.83 μs) and without blocking. Other investigations GQ1b antibody level was prominent – 315.7% (norm – up to 9%), antibodies against acetylcholine receptors were not found. MR of brain and thorax were normal. The patient was treated with a series of plasma exchange. After 14 days he began to walk with crutches and ptosis and diplopia significantly decreased. 6 weeks later he was able to walk without support and oculomotor function normalized. Neurophysiological findings in MFS are discussed. Conclusion In our patient with MFS we diagnosed presynaptic type (axonal) disorder of neuromuscular transmission.